PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 63 PEKANBARU - Mutiara, Mutiara; Witri, Gustimal; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract.This study was conducted based problems of poor learning outcomes of students in science subjects. Of the 22 students obtained an average grade of 65,45 and 50% of students have not reached a value above the minimum completeness criteria (KKM) has been established, while the KKM predetermined namely 70. This research aims to improve learning outcomes fifth grade science students Elementary School 63 Pekanbaru through the application of the model Quantum Teaching. The shape of this study is a collaborative action research. Said to be collaborative because in this study the researchers in collaboration with the other fifth grade teacher. This research was conducted at the State Elementary School 63 Pekanbaru. While the study period starting from January through April 2016. As the subjects in this study were teachers and students of class V SD Negeri 63 Pekanbaru school year 2015/2016 the number of students as many as 22 people consisting of 8 boys and 14 female student. Based on the results of research and pembahsan it can be concluded that the application of Quantum Teaching learning model can improve student learning outcomes. Learning outcome from a base score to the first cycle that of the average of 65,45 to 72,50 with a 10,77% increase. IPA learning outcome from a base score to the second cycle that is average to 72,95 with an increase of 11,46%. This means that the application of Quantum Teaching learning model can improve student learning outcomes.Key Words: Quantum Teaching, Learning Outcomes IPA.